Changed expression of E-cadherin and Galectin-9 in oral squamous cell carcinomas but lack of potential as prognostic markers - Chang, S.W.; Kallarakkal, T.G.; Abraham, M.T. (Asian Pacific Education Press Ltd., 2014)
Background: The survival rate for oral squamous cell carcinoma (OSCC) has remained generally unchanged in the past three decades, underlining the need for more biomarkers to be developed to aid prognostication and effective management. The prognostic potential of E-cadherin expression in OSCCs has been variable in previous studies while galectin-9 expression has been correlated with improved prognosis in other cancers. The aim of the present study was to investigate the expression of galectin-9 and E-cadherin in OSCC and their potential as prognostic biomarkers. Materials and Methods: E-cadherin and Galectin-9 expression was examined by immunohistochemistry in 32 cases of OSCC of the buccal mucosa (13 with and 19 without lymph node metastasis), as well as 6 samples of reactive lesions and 5 of normal buccal mucosa. Results: The expression of E-cadherin in OSCC was significantly lower than the control tissues but galectin-9 expression was conversely higher. Median E-cadherin HSCOREs between OSCCs positive and negative for nodal metastasis were not significantly different. Mean HSCOREs for galectin-9 in OSCC without lymph node metastasis (127.7 +/- 81.8) was higher than OSCC with lymph node metastasis (97.9 +/- 62.9) but this difference was not statistically significant. Conclusions: E-cadherin expression is reduced whilst galectin-9 expression is increased in OSCC. However, the present results suggest that E-cadherin and galectin-9 expression may not be useful as prognostic markers for OSCC.